Brain injury following trial of hypothermia for neonatal hypoxic–ischaemic encephalopathy. Issue 6 (18th October 2012) - Shankaran, Seetha; Barnes, Patrick D; Hintz, Susan R; Laptook, Abbott R; Zaterka-Baxter, Kristin M; McDonald, Scott A; Ehrenkranz, Richard A; Walsh, Michele C; Tyson, Jon E; Donovan, Edward F; Goldberg, Ronald N; Bara, Rebecca; et al.
Abstract : Objective: The objective of our study was to examine the relationship between brain injury and outcome following neonatal hypoxic–ischaemic encephalopathy treated with hypothermia. Design and patients: Neonatal MRI scans were evaluated in the National Institute of Child Health and Human Development (NICHD) randomised controlled trial of whole-body hypothermia and each infant was categorised based upon the pattern of brain injury on the MRI findings. Brain injury patterns were assessed as a marker of death or disability at 18–22 months of age. Results: Scans were obtained on 136 of 208 trial participants (65%); 73 in the hypothermia and 63 in the control group. Normal scans were noted in 38 of 73 infants (52%) in the hypothermia group and 22 of 63 infants (35%) in the control group. Infants in the hypothermia group had fewer areas of infarction (12%) compared to infants in the control group (22%). Fifty-one of the 136 infants died or had moderate or severe disability at 18 months. The brain injury pattern correlated with outcome of death or disability and with disability among survivors. Each point increase in the severity of the pattern of brain injury was independently associated with a twofold increase in the odds of death or disability. Conclusions: Fewer areas of infarction and a trend towards more normal scans were noted in brain MRI following whole-body hypothermia. Presence of the NICHD pattern of brain injury is a marker of death or moderate or severe disability at 18–22 months following hypothermia for neonatal encephalopathy.